'Real‐life' effectiveness studies of omalizumab in adult patients with severe allergic asthma: systematic review. Issue 5 (25th February 2016) - Abraham, I.; Alhossan, A.; Lee, C. S.; Kutbi, H.; MacDonald, K.
Abstract: We reviewed 24 'real‐life' effectiveness studies of omalizumab in the treatment of severe allergic asthma that included 4117 unique patients from 32 countries with significant heterogeneity in patients, clinicians and settings. The evidence underscores the short‐ and long‐term benefit of anti‐IgE therapy in terms of the following: improving lung function; achieving asthma control and reducing symptomatology, severe exacerbations and associated work/school days lost; reducing healthcare resource utilizations, in particular hospitalizations, hospital lengths of stay and accident specialist or emergency department visits; reducing or discontinuing other asthma medications; and improving quality of life – thus confirming, complementing and extending evidence from randomized trials. Thus, omalizumab therapy is associated with signal improvements across the full objective and subjective burden of illness chain of severe allergic asthma. Benefits of omalizumab may extend up to 2–4 years, and the majority of omalizumab‐treated patients may benefit for many years. Omalizumab has positive short‐ and long‐term safety profiles similar to what is known from randomized clinical trials. Initiated patients should be monitored for treatment response at 16 weeks. Those showing positive response at that time are highly likely to show sustained treatment response and benefit in terms of clinical, quality of life and health resource utilization outcomes.